Crisis in the structure of land freight transporte sector in Colombia in the last five years (2014)
The last doccument has the objective to detect and characterize some of the couses of the terrestrial load transporting and structuring crisis of Colombia as well as posible solutions. This assay conteins an state of art that explains how has been the behavior of some ítems as highways, politic structure, job development, vehicule fleets, loads management, loading centers, and transporting regions; by this study we can affirm that we are certainly are a transporting economy by excellence, but the biggest trouble of this era for us was to make grow the international transport with our neightbor countries, developing too a transporting fleet with trained drivers. We propoused as a solution a “petra” plan formuled by the Spanish government wich unexplainly hasn ́t working properly, and characterizes some of the solutions to the crisis of this economy place that can be, changes on the “auto boss” sistem, often training for drivers, an integral visión of the economic place, clear and strong legislation, an implementation and use of the communication tecnologies, evolution of logidtic opperators, fleet arrange, and of course implementation of clean technologies. We conclude that this sector moves our economy not only with load transport but as a regional and family fact, and it is suggested to apply this solutions, and keep his support and developing.